THE IMPACT OF SOCIO-PSYCHOLOGICAL FACTORS ON THE FORMATION OF AGGRESSIVE BEHAVIOR IN ADOLESCENCE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the influence of socio-psychological factors on the formation of aggressive behavior during adolescence. The study analyzes the role of family environment, peer relationships, school environment, and mass media in shaping adolescents’ aggressive behavior. The impact of socio-psychological factors on physical, verbal, and indirect aggression is explored. The research findings provide practical recommendations for developing psychological prevention and correction methods.The article serves as a valuable resource for psychologists, educators, and parents.